Healthy Living: Staying Regular - Linda B. Bobroff; Luisa Oliver-Cordero (EDIS)
Having a bowel movement fewer than three times a week is defined as constipation. This condition is very common in persons over age 65. Over time, chronic constipation can cause serious and painful conditions such as hemorrhoids and diverticular disease. This revised 2-page fact sheet describes the causes, prevention, and high fiber foods. Written by Linda B. Bobroff and Luisa Oliver-Cordero and published by the UF Department of Family Youth and Community Sciences, August 2011.